2009
DOI: 10.1108/03090560910976447
|View full text |Cite
|
Sign up to set email alerts
|

Online grocery shopping: the influence of situational factors

Abstract: Purpose -This paper seeks to understand the triggers which influence the adoption (and the discontinuation) of online grocery shopping. Specifically, the research aims to establish the role of situational factors in the process of adoption. Design/methodology/approach -A two-step research process is employed. First, exploratory qualitative research is carried out, with the purpose of gaining an in-depth understanding of consumers' online grocery shopping behaviour. This is followed by a large-scale quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
197
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(213 citation statements)
references
References 29 publications
8
197
1
7
Order By: Relevance
“…These resulting indirect effects can be justified as follows. Bell et al (1998) and Hand et al (2009) Beside others personal characteristics age (µ 1 ) can determine the ability to carry out shopper logistics (Keillor et al, 1996;Teller and Gittenberger, 2011). The relevance of the shopping logistics as part of the shopping experience is also strongly dependent on the shopping orientation whereas a hedonic shopping orientation (µ 2 ) decreases the perception of shopping as a burden (e.g., Babin et al, 1994).…”
Section: -------------------------Figure 1 Near Here ----------------mentioning
confidence: 99%
“…These resulting indirect effects can be justified as follows. Bell et al (1998) and Hand et al (2009) Beside others personal characteristics age (µ 1 ) can determine the ability to carry out shopper logistics (Keillor et al, 1996;Teller and Gittenberger, 2011). The relevance of the shopping logistics as part of the shopping experience is also strongly dependent on the shopping orientation whereas a hedonic shopping orientation (µ 2 ) decreases the perception of shopping as a burden (e.g., Babin et al, 1994).…”
Section: -------------------------Figure 1 Near Here ----------------mentioning
confidence: 99%
“…For now, however, taste, smell and touch cannot be experienced virtually. For example, Hand et al (2009) found that online grocery shoppers missed the experience of selecting produce and foods themselves. A generous return policy is also helpful in diminishing the risk of buying an untried experience product (Zeng & Xu, 2010).…”
Section: Experience Productsmentioning
confidence: 99%
“…Shopping agents will be particularly useful for price-adverse consumers (Pathak, 2010). Shopping online for necessities such as groceries is more often the result of circumstances such as illness, lack of transportation or convenience "rather than by a cognitive elaboration and decision process" (Hand et al, 2009(Hand et al, , p. 1215. If their circumstances improve, consumers will often stop shopping online for these necessities, especially if they perceived a lack of service quality (Hand et al, 2009).…”
Section: Necessitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Home delivery of items purchased online is appealing to those for whom going out to shop is difficult for various reasons, such as physical disability, the need to care for small children, the lack of adequate or convenient transportation, and/or a busy lifestyle. Buying groceries and other products online unchains consumers from physically driving to and shopping in traditional stores [19].…”
Section: Introductionmentioning
confidence: 99%